Flow and Transport in Subsurface Environment (Springer Transactions in Civil and Environmental Engineering,, 2018)
This book presents a collection of contributions from experts working on flow and transport in porous media around the globe. The book includes chapters authored by engineers, scientists, and mathematicians on single and multiphase flow and transport in homogeneous as well as heterogeneous porous media. Addressing various experimental, analytical, and modeling aspects of transport in sub-surface domains, the book offers a valuable resource for graduate students, researchers, and professionals alike.